2012
DOI: 10.1155/2012/913807
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Effects of Mandibular Distraction Osteogenesis on Developing Deciduous Molar Teeth

Abstract: Background. Many studies have demonstrated the effectiveness of mandibular distraction osteogenesis (MDO) in alleviating the micrognathia-associated upper airway obstruction but very few studies have focused on long-term dental outcomes. Objective. To report the effect of MDO on developing deciduous molars in the distraction area. Methods. A retrospective chart review was performed to identify patients with Pierre Robin sequence who underwent MDO with documented long-term dental assessments. Results. Ten child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 15 publications
2
27
0
Order By: Relevance
“…23 Hong et al revealed the results of an internal nonresorbable device applied for treatment of Robin sequence infants (mean age, 2.3 months; follow-up, 3 to 5 years). 24 Thirty percent of cases developed root malformations and positional changes of deciduous second molars, which is comparable to our findings when looking only at second deciduous molars. 24 However, in that study, the dental developmental stage was primary dentition: information on possible damage to permanent molars was lacking.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…23 Hong et al revealed the results of an internal nonresorbable device applied for treatment of Robin sequence infants (mean age, 2.3 months; follow-up, 3 to 5 years). 24 Thirty percent of cases developed root malformations and positional changes of deciduous second molars, which is comparable to our findings when looking only at second deciduous molars. 24 However, in that study, the dental developmental stage was primary dentition: information on possible damage to permanent molars was lacking.…”
Section: Discussionsupporting
confidence: 90%
“…24 Thirty percent of cases developed root malformations and positional changes of deciduous second molars, which is comparable to our findings when looking only at second deciduous molars. 24 However, in that study, the dental developmental stage was primary dentition: information on possible damage to permanent molars was lacking. 24 In preventing damage to molar buds, the position of the osteotomy and screws must be considered.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations